Meta-Analysis of the Effect of Exposure to Indoor Cigarette Smoke in Pregnant Women on the Risk of Infants Low Birth Weight - Dinda Nur Asri Mutiara Ramadhani; Uki Retno Budhiastuti; Bhisma Murti (Masters Program in Public Health, 2023)
Background: Problems related to low birth weight are often found in developing countries. Expo-sure to cigarette smoke is one of the factors causing low birth weight, in this case caused by the chemicals in cigarettes which affect the health of pregnant women and babies. This study aims to determine the effect of exposure to secondhand smoke in the home on pregnant women on the risk of giving birth to babies with low birth weight. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: pregnant women. Intervention: exposure to household ciga-rette smoke is high. Comparison: household exposure to secondhand smoke is low. Outcome: low birth weight. The databases used are PubMed, Google Scholar, and Science Direct with keywords (“Pregnancy Women” OR “Passive Smoking” OR “Low Birth Weight”) AND “Case Control Study”. A total of 9 articles met the inclusion criteria, namely primary full text paper, case-control design, adjus-ted Odds Ratio (aOR), research subjects of pregnant women, interventions in the form of high cigarette smoke exposure, and outcomes in the form of low birth weight for analysis carried out with RevMan 5.3. Results: A meta-analysis has been carried out on 9 articles with a case-control study design from the Asian Continent and the African Continent in pregnant women with a sample size of 4,244. The results of the meta-analysis showed that pregnant women who were exposed to secondhand smoke from the environment had a risk of giving birth to babies with low birth weight 1.82 times compared to those not exposed to secondhand smoke and the effect of exposure was statistically significant (aOR= 1.82; 95% CI= 1.54 to 2.16; p <0.001). Conclusion: The effects of exposure to cigarette smoke in pregnant women can increase the risk of low birth weight babies. Keywords: passive smokers, low birth weight, pregnant women, babies, Correspondence:Dinda Nur Asri Mutiara Ramadhani. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: mutiaradinda42@gmail.com Mobile: +6282323346406